Great by choice : uncertainty, chaos, and luck-- why some thrive despite them all - Collins, James C. (James Charles), 1958-; Hansen, Morten T. (New York, NY : HarperBusiness, 2011)
"Great by Choice" distinguishes itself from Collins's prior work by its focus not just on performance, but also on the type of unstable environments faced by leaders today. With a team of more than twenty researchers, Collins and Hansen studied companies that rose to greatness--beating their industry indexes by a minimum of ten times over fifteen years--in environments characterized by big forces and rapid shifts that leaders could not predict or control. The research team then contrasted these "10X companies" to a carefully selected set of comparison companies that failed to achieve greatness in similarly extreme environments.
Thriving in uncertainty -- 10xers -- 20 Mile march -- Fire bullets, then cannonballs -- Leading above the death line -- SMaC -- Return on luck -- Epilogue: great by choice -- Frequently asked questions.
Includes bibliographical references (p. 255-293) and index.
Keywords: Success in business -- Case studies; Creative ability in business -- Case studies; Technological innovations -- Management -- Case studies